INTERACTION OF HEAVY METALS IN THE SOIL-PLANT SYSTEM OF URBAN GARDENS IN ATHENS, GREECE - Kazantzoglou, A.; Argyraki, A.; Papageorgiou, S.; Fadel, D. (Bulletin of the Geological Society of Greece, 2016)
Preliminary data on the interaction between soil and edible plants with respect to heavy metal concentrations in Athens, Greece are presented. Concentration ranges of Zn, Cu, Ni, Cr, Co, Mn, Fe, Ba, Pb and Cd in soils and vegetables collected from urban allotments in Athens are determined and assessed taking into account the pseudototal (extracted by aqua regia) and mobilizable (0.43 M acetic acid extractable) concentrations of the elements in the rhizosphere soil of the collected plants as well as the total concentrations in plant tissue. Average elemental concentrations in urban allotments are lower than the ones previously reported for Athens urban soil. No detectable concentrations of the non essential heavy metals Pb and Cd were measured in the studied plants while concentrations of micronutrient elements in plants are within normal ranges. The collected data indicate that previous land use is an important factor controlling heavy metal content in soil and that there is a complex mechanism controlling micronutrient uptake by plants.